Jasmine Toguchi, flamingo keeper - Florence, Debbi Michiko (Florence, Debbi Michiko. Jasmine Toguchi, 2018)
Jasmine makes a wish for a pet flamingo on the special daruma doll her grandmother sent from Japan, then sets out to prove herself responsible enough for a pet.